2020
DOI: 10.1021/acs.nanolett.0c03930
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Fluorescent Gold Nanoclusters Using Xanthate-Functionalized Hydrophilic Polymers: Toward Enhanced Monodispersity and Stability

Abstract: We introduce xanthate-functionalized poly(cyclic imino ethers)s (PCIEs), specifically poly(2-ethyl-2-oxazoline) and poly(2-ethyl-2oxazine) given their stealth characteristics, as an attractive alternative to conventional thiol-based ligands for the synthesis of highly monodisperse and fluorescent gold nanoclusters (AuNCs). The xanthate in the PCIEs interacts with Au ions, acting as a well-controlled template for the direct formation of PCIE-AuNCs. This method yields red-emitting AuNCs with a narrow emission pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…We recently developed a method aiming to overcome these challenges by employing a xanthate-functionalized polymer as a ligand to template and stabilize AuNCs. 6 Poly(cyclic imino ether)s (PCIEs) were designed and synthesized with a xanthate terminal group which served as an attractive alternative to thiolated ligands. The new method yielded a highly monodispersed PCIEs-AuNCs with excellent optical properties such as narrow emission (λ em = 645 nm), long fluorescence decay time (∼722−844 ns), and good quantum yield (4.3−4.8%).…”
Section: ■ Why the Synthetic Route Matters?mentioning
confidence: 99%
See 2 more Smart Citations
“…We recently developed a method aiming to overcome these challenges by employing a xanthate-functionalized polymer as a ligand to template and stabilize AuNCs. 6 Poly(cyclic imino ether)s (PCIEs) were designed and synthesized with a xanthate terminal group which served as an attractive alternative to thiolated ligands. The new method yielded a highly monodispersed PCIEs-AuNCs with excellent optical properties such as narrow emission (λ em = 645 nm), long fluorescence decay time (∼722−844 ns), and good quantum yield (4.3−4.8%).…”
Section: ■ Why the Synthetic Route Matters?mentioning
confidence: 99%
“…While proteins provide certain advantages such as allowing a one-pot synthesis approach in aqueous solution–mostly advantageous for biomedical applications–protein-protected AuNCs are a complex marriage hard to structurally characterize, making their structure–property relationship difficult to predict or elucidate . This is why the use of other ligands such as polymers, , including dendrimers, peptides, , including single amino acids, and DNA to synthesize AuNCs is emerging in the literature (Figure E,F), as they offer a higher degree of programmability. For example, by manipulating the nature of the polymer, peptide, or DNA, the metal–ligand charge transfer can be optimized toward a maximized photoluminescence …”
Section: Understanding Structure–property Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Meanwhile, the monodisperse NCs are easily obtained via various synthesis strategies (microwave-assisted methods, 5 hydrothermal, 6 heating and stirring method, 7 etc.) and numerous ligands (thiolates, 8 peptides, 9 proteins, 10 polymers, 11 and phosphines 12 ). However, inhomogeneous and low quantum yields (QYs) of NCs greatly restrict their optical applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Still, studies of AuNCs on OP screening are scarcely reported. To the best of our knowledge, only 12 related works have been reported. However, most of them (10) detect OPs through the unique response of signalers to thiocholine and require additional quenchers, and the other two sensors are built based on OPs’ depression on trypsin or alkaline phosphatase activity, which might not like AChE to be specifically inhibited by OPs. , In addition, most of the AuNCs are prepared using monothiol compounds, BSA, and polyethyleneimine as reductants and only have −OH, −NH 2 , and −COOH groups; thus, developing AuNCs with new functionalized groups is in high demand.…”
Section: Introductionmentioning
confidence: 99%